Optimization of heat and mass transfer processes in air conditioning systems in public buildings - A. V. Tsygankov; V. I. Lysev; A. K. Rubtsov; A. S. Shilin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Increasing the energy efficiency of air conditioning systems in public buildings and structures is an actual task. A mathematical model is proposed for determining the values of internal air temperatures and temperatures of the surfaces of enclosure in order to calculate the predicted values of heat fluxes in buildings and structures. An experimental study has been carried out showing the relevance of the proposed method